ECONOMIC EFFICIENCY AND PRODUCTIVITY OF THE FISHING BOAT FOR GIANT THREADFISH (Eletheronema tetradactylum) - Muchtar Ahmad; . Nofrizal (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
This paper discussed the productivity and economic efficiency of the fishing boat for giant threadfish (Eletheronema tetradactylum), which operated in the Malacca Straits. Eleven fishing boats with different weights (GT) were observed for their input as total cost and output as total benefit in order to calculate respective fishing boat productivity and  efficiency. It was found that fishing boat activities on giant threadfish using various boat sizes were efficient with BCR>1 and profitable.  However, the average economic efficiency of all boats was 1.65 with the highest efficiency of 1.74 for the 2 GT fishing boat.  The average productivity of the fishing boat was Rp 4.5 million or Rp 1.5 million/GT with its capital payback period of 29 months.The highest productivity was found on the 2 GT fishing boat of Rp 5.5 million or Rp 2.8 million/GT with its capital payback period of 27 months. However, The 4 GT fishing boat was recommended to be developed for artisanal fishery of giant threadfish because its economic efficiency was relatively high of 1.71 and its produktivity was Rp 5.1 million or Rp 1.3 million/GT with capital payback period of 29 months.   Keywords: economic efficiency, fishing boat,  Eletheronema tetradactylum, payback period